eSports evolution in football game series - Zagala, K.; Strzelecki, A. (Physical Culture and Sport. Studies and Research, 2019)
Sport used to be practiced and watched only live. Over time, it started to be broadcast by the radio or television. The development of sport on the Internet has led to the emergence of eSports and professionalization of virtual sports competitions. For some gamers playing computer games has turned into competition and later into the professionalization of the game. This paper explores the topic of electronic sports and virtual competition. It discusses eSports and the accompanying behaviors and practices. Authors delivered taxonomy of video game types, game modes and current phenomenon of both online and land-based tournaments as well eSports leagues. The paper also illustrates how gamers are preparing themselves for tournaments and a crucial role of gamers` motivation. Authors present the FIFA football games series and its eSports application. The adopted research method allowed to obtain answers from n=452 gamers. Results show that 60% of gamers have been spending more than 7 hours a week playing games. More than half of gamers have been playing for more than ten years. Most players play in games because it is considered as a hobby. Most of the gamers consider eSports as a sport. Most of the players are also spectators, who had watched in streaming at least one eSports tournament We find that FIFA game series has an extensive eSports platform and filled the gap by exploring it. Gamers usually play 40 games each weekend in FIFA eSports league but casual eSports gamers and spectators rarely take part in land-based tournaments.